(11b-4)-5(2b+1)=-5

Simple and best practice solution for (11b-4)-5(2b+1)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (11b-4)-5(2b+1)=-5 equation:


Simplifying
(11b + -4) + -5(2b + 1) = -5

Reorder the terms:
(-4 + 11b) + -5(2b + 1) = -5

Remove parenthesis around (-4 + 11b)
-4 + 11b + -5(2b + 1) = -5

Reorder the terms:
-4 + 11b + -5(1 + 2b) = -5
-4 + 11b + (1 * -5 + 2b * -5) = -5
-4 + 11b + (-5 + -10b) = -5

Reorder the terms:
-4 + -5 + 11b + -10b = -5

Combine like terms: -4 + -5 = -9
-9 + 11b + -10b = -5

Combine like terms: 11b + -10b = 1b
-9 + 1b = -5

Solving
-9 + 1b = -5

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 1b = -5 + 9

Combine like terms: -9 + 9 = 0
0 + 1b = -5 + 9
1b = -5 + 9

Combine like terms: -5 + 9 = 4
1b = 4

Divide each side by '1'.
b = 4

Simplifying
b = 4

See similar equations:

| 2x^7+2x^6-4x^5= | | (9x-9/7)+(8-x/3)=9 | | 9x+5x+3+8=11x+4+2x | | 33*w=52 | | (6x^2+22+17)/(x+3) | | w*2w-5=52 | | 2w^2-5w-17-w^2+2w-1=0 | | 2w^2-5w-17-w^2+2w-1=00 | | 2u^2-24u+70-u^2+14u-49=0 | | 2w^2-3w-16-w^2+4w-4=0 | | 2x^2-8x-8-x^2+4x-4=0 | | (x+2)/(x-6)=55 | | 2v^2+v+30-v^2+8v-16=0 | | 2y^2-3y+5-y^2+6y-9=0 | | 2m-4+12=3m-4+2 | | 2y^2-3y+5-y^2-6y+9=0 | | 2y^2-3y+5+y^2-6y+9=0 | | 24x^2-49x-40=0 | | 2m-4+12=2m-4+12 | | -12x^2+45x+12=0 | | 2y^2-y-29-y^2+2y-1=0 | | 2v^2+9v+10-v^2-4v-4=0 | | -z=6z-5 | | 6d-5=25 | | (7-u)(3u+8)=0 | | -2x-13=9x+9 | | 1/2x27x24 | | x^2+6xy+8y^2=0 | | 100x=7(24.99) | | (3+5)*(14-9)= | | 100x=5.5(125) | | 100x=6(95) |

Equations solver categories